2021
DOI: 10.1021/jacs.1c07983
|View full text |Cite
|
Sign up to set email alerts
|

An Expanded SET Model Associated with the Functional Hindrance Dominates the Amide-Directed Distal sp3 C–H Functionalization

Abstract: The mechanistic understanding of catalytic radical reactions currently lags behind the flourishing development of new types of catalytic activation. Herein, an innovative single electron transfer (SET) model has been expanded by using the nonadiabatic crossing integrated with the rate-determining step of 1,5-hydrogen atom transfer (HAT) reaction to provide the control mechanism of radical decay dynamics through calculating excited-state relaxation paths of a paradigm example of the amide-directed distal sp 3 C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 92 publications
2
12
0
Order By: Relevance
“…The predicted λ max is closely correlated to experimentally measured values for 2 a and 2 b (452–457 nm) , as well as the irradiation wavelength (456 nm) used for the photosensitized nitrene generation in Chang’s study . Similar to our previous computations, ,, MLCT absorption bands of Ru-based complexes studied here also originate from the strong coupling among all possible electron transitions from metal to various ligands, which provides a potential way to tune the intensity of the maximum MLCT absorption of photocatalysts.…”
Section: Results and Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…The predicted λ max is closely correlated to experimentally measured values for 2 a and 2 b (452–457 nm) , as well as the irradiation wavelength (456 nm) used for the photosensitized nitrene generation in Chang’s study . Similar to our previous computations, ,, MLCT absorption bands of Ru-based complexes studied here also originate from the strong coupling among all possible electron transitions from metal to various ligands, which provides a potential way to tune the intensity of the maximum MLCT absorption of photocatalysts.…”
Section: Results and Discussionsupporting
confidence: 87%
“…The predicted λ max is closely correlated to experimentally measured values for 2 a and 2 b (452−457 nm) 46,47 as well as the irradiation wavelength (456 nm) used for the photosensitized nitrene generation in Chang's study. 67 Similar to our previous computations, 68,69,72 MLCT absorption bands of Rubased complexes studied here also originate from the strong coupling among all possible electron transitions from metal to various ligands, which provides a potential way to tune the intensity of the maximum MLCT absorption of photocatalysts. It is worth noting that previous experiments have revealed that this photosensitized C−H amidation reaction takes place in high yields both in the gas phase (70%) and in a weakly polar environment (1,1,2,2-tetrachloroethane: 75%; dichloromethane: 70%), while it is less effective in polar media (acetonitrile: 9%; N,N-dimethylformamide: <5%).…”
Section: Photophysical Properties Of the Substrate And The Photosensi...supporting
confidence: 85%
See 1 more Smart Citation
“…Once dismissed as unselective and suitable only for initiating polymerization, in recent years there has been enormous progress toward taming free radicals for applications in target synthesis. Critical to their success has been the development of powerful but highly selective methods for radical generation, particularly using photochemistry, electrochemistry, organic superelectron donors, and transition metal catalysis. Nonetheless, the discovery of new strategies of radical generation, particularly under light-free, electricity-free, metal-free conditions, remains crucial. Organocatalysis, particularly involving N-heterocyclic carbenes (NHCs), shows promise approach for realizing radical generation and radical–radical cross-coupling. However, to develop this chemistry, a greater understanding of how they mediate electron transfer is critical.…”
Section: Introductionmentioning
confidence: 99%
“…However, the HMO calculations are not accurate due to the nature of semi-empirical quantum chemical calculations. To solve this issue and promoted by our interest in organocatalysis 46,[60][61][62][63][64] and theoretical research experiences, [65][66][67][68][69] we believe that the DFT version of the HFV index should be more suitable to predict the actual active site of the organocatalytic reaction systems, in which the chemoselectivity is generally associated with the different active sites of the conjugated structures of the reactants or intermediates. As depicted in Scheme 1, the HFV index (denoted as F i ) represents the activity of the i atom obtained by the maximum π bond order of benchmark trimethylenemethane minus its related π bond orders, and the HFV index of the active carbon atom is obtained using F i = P max − P P ij .…”
Section: Introductionmentioning
confidence: 99%